EFL Teaching Method for Young Learners in Digital Era - Ummi Ashim Azzahra (Indonesia Technology-Enhanced Language Learning (iTELL) Journal, 2024)
Teaching English to young pupils in the digital age requires innovative methods considering their psychological characteristics. The most crucial factors for teaching English to young learners, particularly those between the ages of four and five, are selecting the right teaching strategy and handling techniques for the classroom and choosing instructional materials that complement these strategies. This study has two main goals: first, to identify the English teaching methodology being employed at Beetle Bug Bilingual Kindergarten Semarang; second, to provide an explanation of the method's rationale based on a review of the literature, highlighting both the method's strengths and areas for improvement. This is observation-based research in which all of the results are discussed qualitatively. The study found that the teacher combined Communicative Language Teaching with the Situational Language Teaching method. She employed creative strategies to capture the students' attention during their lessons because they were still learning to write the alphabet. The fact that there was no crying or disruption during the education process indicates that the students exhibited good conditioning.